Human development report 2005 : international cooperation at a crossroads : aid, trade and security in an unequal world.. - United Nations Development Programme ([New York: Oxford University Press], 2005)
"This year's Human Development Report takes stock of human development, including progress towards the MDGs. Looking beyond statistics, it highlights the human costs of missed targets and broken promises. Extreme inequality between countries and within countries is identified as one of the main barriers to human development - and as a powerful brake on accelerated progress towards the MDGs." "New approaches to international cooperation are vital if the promise of the Millennium Declaration is to be realized. Practical action is needed to make the next 10 years a "decade for development." Focusing on aid, trade and security, three of the central pillars of international cooperation, Human Development Report 2005 sets out a bold analysis of the problems and identifies solutions. It argues that rich countries need to move beyond encouraging words to align their policies with the commitments made in the Millennium Declaration."--BOOK JACKET.
Overview: International cooperation at a crossroads : aid, trade and security in an unequal world -- ch. 1. The state of human development -- ch. 2. Inequality and human development -- ch. 3. Aid for the 21st century -- ch. 4. International trade : unlocking the potential for human development -- ch. 5. Violent conflict : bringing the real threat into focus -- Human development indicators.
Errata inserted.
"Published for the United Nations Development Programme (UNDP)."
Includes bibliographical references (p. 188-207).
Keywords: Internationale samenwerking; Desenvolvimento econ?omico.; Indicadores sócio-econ?omicos.; Desenvolvimento humano; Justi?ca social; Coopera?c?ao internacional; Qualidade de vida; Social indicators; International trade; Quality of life; Security, International; Economic development -- -- Social aspects